Effects of the Insertion Type and Depth on the Pedicle Screw Pullout Strength: A Finite Element Study - K. Jendoubi; Y. Khadri; M. Bendjaballah; N. Slimane (Applied Bionics and Biomechanics)
Purpose. The pedicle screw is a surgical device that has become widely used in spinal fixation and stabilization. Postsurgical complications such as screw loosening due to fatigue loading and screw breakage still need investigations. Clinical parameters such as the screw insertion type and depth, the bone density, and the patient degree of mobility greatly affect the mechanisms of the implant’s failure/success. Methods. The current finite element study focused on the prediction of the pedicle screw pullout strength under various conditions such as insertion type, insertion depth, bone quality, and loading mode. Results. As depicted in this study, the preservation of the pedicle cortex as in the N1 insertion technique greatly enhances the pullout resistance. In addition, the higher the screw-anchoring depth, permitting to gear a maximum number of threads, the better the protection against premature breakouts of pedicle screws. Conclusions. In agreement with experimental data, the type of insertion in which the first screw thread is placed immediately after the preserved pedicle cortex showed the best pullout resistance for both normal and osteoporotic bone.